The Effects of Cranial Cryotherapy on Hemodynamics and Cognition in Healthy Adults. Issue 11 (2020) - Lempke, Landon B.; Fraser, John J.; Erdman, Nicholas K.; Barone, Nicholas A.; Saliba, Susan; Resch, Jacob E.
ABSTRACT: Purpose: This study aimed to determine the effects of superficial cranial cryotherapy on cortical hemodynamics and neurocognitive performance in healthy young adults. Methods: Thirty-four healthy individuals (21.3 ± 1.6 yr; 173.8 ± 10.6 cm; 73.3 ± 12.5 kg) participated. Cortical hemodynamic changes over the left prefrontal cortex was assessed using functional near-infrared spectroscopy (fNIRS) throughout the study timeline. All participants were seated in a quiet room and for a 5-min period of cognitive rest before administration of the Stroop Test (CNS Vital Signs) followed by another 5-min period of cognitive rest. Participants were randomized a priori to either the cryotherapy (CryoHelmet™) or control group for 20 min while seated in an isolated quiet room. After the intervention, each group completed a 5-min cognitive rest period, a postintervention Stroop Test, and a final 5-min cognitive rest period. Repeated-measures ANOVA was used to assess cortical hemodynamics (oxygenated hemoglobin, deoxygenated hemoglobin) and Stroop Test outcome scores across time (pre– and post–Stroop Test administration, during intervention, and before and after intervention). Results: No significant group–time interactions were observed between groups for oxygenated hemoglobin or deoxygenated hemoglobin ( P > 0.05). Cryotherapy participants committed significantly fewer Stroop Test errors than did control participants after intervention (0.7 ± 0.26 vs 1.2 ± 0.23; P = 0.05, η 2 p = 0.12). Conclusions: Superficial cranial cryotherapy did not significantly influence cortical hemodynamics in this healthy sample. Statistically significant improvements in neurocognitive performance in the intervention group occurred but are negligible in their clinical meaningfulness. Future studies should examine cortical hemodynamic change in pathological populations and determine the clinical utility of superficial cranial cryotherapy.